The Influence of Corporate Reputation and Stakeholder Involvement on Financial Performance with Corporate Social Responsibility as an Intervening Variable - Dearani, Ninka; Mujanah, Siti; Fianto, Achmad Yanu Alif (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to examine the impact of corporate reputation and stakeholder involvement on financial performance, with Corporate Social Responsibility (CSR) serving as an intervening variable. CSR, which reflects a company’s social responsibility, is suspected of acting as a bridge that strengthens the relationship between corporate reputation and stakeholder involvement, and financial performance. In the highly competitive business era, corporate reputation and stakeholder involvement, particularly in achieving optimal financial performance, are important factors that influence a company’s success. The study uses secondary data from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) and employs path analysis to test the causal relationships between variables. The results show that corporate reputation has a significant effect on financial performance, stakeholder involvement has no effect on financial performance and hypothesis testing using path analysis shows that CSR cannot mediate the relationship between corporate reputation and stakeholder involvement on financial performance.